The ‘empty choice’: A sociological examination of choosing medical research participation in resource-limited Sub-Saharan Africa. - Kingori, Patricia (Current Sociology, 2015)
This article explores the views of frontline research staff in different Sub-Saharan African contexts on the notion of choice in biomedical research. It argues that the current emphasis on individual choice, in the conduct of biomedical research, ignores significant structural and contextual factors in resource-limited settings. These factors severely constrain individual options and often make biomedical research enrolment the most amenable route to healthcare for the world’s poorest. From the position of frontline research staff, local contextual factors and structural issues narrowly frame the parameters within which many prospective participants are asked to choose, to such an extent that individuals are effectively presented with an ‘empty choice’. The article draws on ethnographic and interview data and insights gained through graphic elucidation techniques. It demonstrates that for frontline research staff, macro-level structural factors and their bearing on everyday realities shape what choice in biomedical research participation means in practice.